2019
DOI: 10.1007/s11207-019-1539-y
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis and Catalog of Non-polar Coronal Holes Covering the SDO-Era Using CATCH

Abstract: Coronal holes are usually defined as dark structures seen in the extreme ultraviolet and X-ray spectrum which are generally associated with open magnetic fields. Deriving reliably the coronal hole boundary is of high interest, as its area, underlying magnetic field, and other properties give important hints as regards high speed solar wind acceleration processes and compression regions arriving at Earth. In this study we present a new threshold-based extraction method, which incorporates the intensity gradient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 64 publications
1
82
0
Order By: Relevance
“…The total area covered by long-lived magnetic elements with lifetimes > 4 days is strongly correlated with the unbalanced magnetic flux of CHs (cc = 0.99). These magnetic elements account for ≈ 68% of the unbalanced "open" magnetic flux of CHs at typical coverages of about 3% of the total CH area (Hofmeister et al, 2019;Heinemann et al, 2019). Heinemann et al (2018a,b) investigated a long-lived low-latitude CH observed by the Solar Dynamics Observatory (SDO) and Solar Terrestrial Relations Observatory (STEREO) spacecraft over ten solar rotations from February 2012 to October 2012 (see Figure 7).…”
Section: Introductionmentioning
confidence: 99%
“…The total area covered by long-lived magnetic elements with lifetimes > 4 days is strongly correlated with the unbalanced magnetic flux of CHs (cc = 0.99). These magnetic elements account for ≈ 68% of the unbalanced "open" magnetic flux of CHs at typical coverages of about 3% of the total CH area (Hofmeister et al, 2019;Heinemann et al, 2019). Heinemann et al (2018a,b) investigated a long-lived low-latitude CH observed by the Solar Dynamics Observatory (SDO) and Solar Terrestrial Relations Observatory (STEREO) spacecraft over ten solar rotations from February 2012 to October 2012 (see Figure 7).…”
Section: Introductionmentioning
confidence: 99%
“…Any instrument (in this case AIA) suffers inevitable depletions (e.g., decreasing sensitivity, aging filters, and others), distortion of optical system, and scattered light to name just a few. But in the context of this study, especially regarding the CH detection, we do not believe that these uncertainties introduce significant errors, as each CH was manually tuned to account for such instrumental and observational changes (see for more details Heinemann et al, ). For the case of large CHs we have only one point so the relation between coverage and area remains inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…The CH boundaries were extracted using catch (Heinemann et al, 2019), an intensity threshold algorithm that is modulated by the intensity gradient along the CHs boundary. The SSW-IDL-written GUI enables the user to optimize the threshold used for the CH extraction by considering the average intensity profile at the Journal of Geophysical Research: Space Physics 10.1029/2019JA027173 boundary to find the highest gradient.…”
Section: Extracting Ch Boundaries With Catchmentioning
confidence: 99%
See 2 more Smart Citations